Regional science-based clusters:a case study of three European concentrations - Teräs, J. (Jukka) (University of Oulu, 2008)
Abstract The aim of this thesis is to provide an improved understanding of the structural characteristics and the dynamic evolution of regional science-based clusters. The study is based on an in-depth comparison of three non-metropolitan science-based clusters: Oulu in Finland, Luleå in Sweden, and Pisa in Italy. This thesis is the result of a qualitative multiple-case study consisting of in-depth interviews with cluster decision-makers and experts in Finland, Sweden and Italy. The thesis is structured as follows: first the theoretical framework and research method are presented, then the case study regions and clusters are described, and finally, the data from the interviews are collated and discussed. The results of the study suggest that regional science-based clusters are not isolated entities but are increasingly more connected to the external environments and global markets than before although the local cluster activities and the "social glue" between the cluster actors are still relevant. The current structures of the clusters should have more alternatives and allow more flexibility. The data from this case study, based not only on the current status of the case clusters but also on a more longitudinal approach, confirm the life cycle nature of regional science-based clusters, consisting of various stages. The results of the study show that a detailed analysis of the cluster components is more efficient than studying the cluster as an aggregate. Furthermore, the data indicate that critical mass plays an important role especially in the development of regional science-based clusters in non-metropolitan regions. This study suggests an optimal size for the non-metropolitan cluster, i.e. one which reaches the critical size of a cluster but avoids the problems related to metropolitan clusters. The study underlines the importance of cluster features, such as cluster leadership and strategic management. The study identified similarities between the case study clusters in Oulu, Luleå, and Pisa, such as e.g. a ...